Heavy Metal Exposure: Molecular Pathways, Clinical Implications, and Protective Strategies - Hajime Koyama; Teru Kamogashira; Tatsuya Yamasoba (MDPI AG, 2024)
Heavy metals are often found in soil and can contaminate drinking water, posing a serious threat to human health. Molecular pathways and curation therapies for mitigating heavy metal toxicity have been studied for a long time. Recent studies on oxidative stress and aging have shown that the molecular foundation of cellular damage caused by heavy metals, namely, apoptosis, endoplasmic reticulum stress, and mitochondrial stress, share the same pathways as those involved in cellular senescence and aging. In recent aging studies, many types of heavy metal exposures have been used in both cellular and animal aging models. Chelation therapy is a traditional treatment for heavy metal toxicity. However, recently, various antioxidants have been found to be effective in treating heavy metal-induced damage, shifting the research focus to investigating the interplay between antioxidants and heavy metals. In this review, we introduce the molecular basis of heavy metal-induced cellular damage and its relationship with aging, summarize its clinical implications, and discuss antioxidants and other agents with protective effects against heavy metal damage.